Sri Lanka's early success in the containment of COVID-19 through its rapid response: Clinical & epidemiological evidence from the initial case series. - Carukshi Arambepola; Nuwan Darshana Wickramasinghe; Surangi Jayakody; Sumudu Avanthi Hewage; Ananda Wijewickrema; Nalika Gunawardena; Sapumal Dhanapala; Shamini Prathapan (PLoS ONE)
Background Despite the rising global burden, Sri Lanka reported a relatively low caseload and mortality (13 deaths as of 20 October 2020) for COVID-19. This warrants exploration of the clinical and epidemiological characteristics of the case series during the initial passive case detection phase in Sri Lanka, in order to understand the success in containment of the disease for more than nine months in the country through its initial early and rapid pandemic response. Methods A retrospective study was conducted using secondary data (hospital records and investigation reports) extracted from all laboratory-confirmed patients admitted to the three main state-sector hospitals in Sri Lanka from 11 March to 7 April 2020. Clinical outcomes were categorized as mild, severe and critical, as per the international classification. Kruskal-Wallis H, Mann Whitney U and Fisher's exact tests compared differences between the variables. Results The case series comprised 146 live discharges and six deaths. Majority were males (63.2%); mean age of 40.9 (SD = 17.9); and symptomatic (72.4%). Sixty-one (40.1%) had co-morbidities, the commonest being diabetes (20.4%) and hypertension (17.8%). Mild (93.4%), severe (2.6%) and critical (4.0%) disease outcomes were noted. Disease severity was significantly higher with older age (p = 0.037), co-morbidities (p = 0.026); and higher white-cell (p = 0.045) and lymphocyte (p = 0.043) counts; but not with being symptomatic (p = 0.683). The commonest symptoms were fever (62.5%), dry cough (48.0%) and sore throat (26.9%). The median duration (IQR) was 3.0 (1.0-5.0) and 18.0 (15.0-29.5) days, respectively before and during hospitalization. Conclusions In contrast to high-risk countries, the younger age, milder disease and low mortality observed in local patients during the initial phase of the pandemic, reflect the early success in containment of the pandemic in Sri Lanka. However, once the disease becomes severe, the factors determining disease fatality remain the same as in other countries. This highlights the value of establishing strong public health systems and disease surveillance in a country, which could provide long-term effects on disease control.